The role of transformational leadership, servant leadership, digital transformation on organizational performance and work innovation capabilities in digital era - Bestadrian Prawiro Theng; Elyzabeth Wijaya; Juliana Juliana; Eddy Eddy; Ali Syah Putra (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2021)
The purpose of this study is to analyze the relationship between Transformational Leadership, Servant Leadership, Digital Transformation on Organizational Performance and Work Innovation Capabilities. In this study using quantitative methods and data analysis techniques Structural Equation Modeling (SEM) using SmartPLS 3.0 software. This research was conducted in the population in this study were all SMEs in Tangerang City as many as 41,155 SMEs and based on the method of determining the number of samples according to Morgan, the sample units were 380 SMEs. Based on the results of data analysis transformational leadership has a significant effect on Organizational Performance, transformational leadership has no significant effect on Work Innovation Capabilities, servant leadership has a significant effect on Organizational Performance, servant leadership has no significant effect on work innovation capabilities, digital transformation has no significant effect on organizational performance, digital Transformation has no significant effect on Work Innovation Capabilities, organizational performance has no significant effect on work innovation capabilities, transformational Leadership has no significant effect on Organizational Performance through Work Innovation Capabilities, Servant Leadership has no significant effect on Organizational Performance through Work Innovation Capabilities, digital transformation has no significant effect significant to the Organizational Performance through Work Innovation Capabilities.